2014
DOI: 10.4067/s0718-58392014000200015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of breed and feeding on the main quality characteristics of sheep carcass and meat: A review

Abstract: This paper reviews two factors (breed and feed) affecting the carcass and meat quality of sheep. The quality of livestock products has acquired greater importance from the distinct perspectives of the different participants in the agricultural food chain. Consumers, producers and the industry give different levels of importance to the parameters of meat and carcass quality. Nevertheless, all the participants in the meat production chain must ensure quality to improve their competitiveness. The quality of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…Nagalakshmi and Reddy () showed higher milk production and feed cost per kg FCM in buffaloes when they were fed PTMR (cotton stalks based), compared to nonpelleted diets. In this study, the PTMR‐fed cows had increased DMI compared to the GTMR‐fed cows, and it resulted in a higher ADG, which was consistent with a report that feeding PTMR mainly affected carcass conformation and several physicochemical parameters, for example fatty acids profile, tenderness and colour of meat quality, of sheep (Ramírez‐Retamal and Morales ).…”
Section: Discussionsupporting
confidence: 91%
“…Nagalakshmi and Reddy () showed higher milk production and feed cost per kg FCM in buffaloes when they were fed PTMR (cotton stalks based), compared to nonpelleted diets. In this study, the PTMR‐fed cows had increased DMI compared to the GTMR‐fed cows, and it resulted in a higher ADG, which was consistent with a report that feeding PTMR mainly affected carcass conformation and several physicochemical parameters, for example fatty acids profile, tenderness and colour of meat quality, of sheep (Ramírez‐Retamal and Morales ).…”
Section: Discussionsupporting
confidence: 91%
“… [ 32 , 35 , 91 , 92 ] Feed Feed has a vital role in affecting physicochemical as well as the organoleptic properties of meat that alternatively affects the quality characteristics [ 93 95 ] Sex of animal Male has thicker subcutaneous fat and more marbling than females. That’s why male presented better quality (flavor) of meat than females [ 96 ] Breed of animal Breed affects fifty-four flavoring compounds of which 75% were Maillard’s reaction products, The IMF content in different breeds of cattle varied from 0.99 to 2.72% [ 10 , 97 , 98 ] Genetic makeup The minor flavor difference among breeds correlated moderately with the marbling factor and is considered to be heritable trait as well [ 38 , 99 ] Age of animal Age affects the solubility of intramuscular collagen and hence increases flavor intensity. Aged animals have higher straight chain fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Physical weakening of structures in the meat, cellular and sub-cellular damage, the release of lysosomes and other proteases, and an increase in protease activity, as well as the muscle protein denaturation at elevated temperatures and low pH, could account for the tenderness of meat. Shear force values of lamb are between 1.84 to 5.0 kg on concentrate, but shear force can go up to 8.7 kg if sheep are on grasslands (Ramirez-Retamal & Morales, 2014). Clelland et al (2018) carried out research with 377 purebred Texel, males and females, and observed shear force values between 2.82 and 3.73 kg, whereas Monteschio et al 2018reported a mean of shear value of 3.65 kg for wethers of similar weight (40 kg) to those used in the present study.…”
Section: Resultsmentioning
confidence: 99%